2019
DOI: 10.5194/gmd-12-2255-2019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sub-shelf melting parameterisations using the ocean–ice-sheet coupled model NEMO(v3.6)–Elmer/Ice(v8.3)

Abstract: Abstract. Oceanic melting beneath ice shelves is the main driver of the current mass loss of the Antarctic ice sheet and is mostly parameterised in stand-alone ice-sheet modelling. Parameterisations are crude representations of reality, and their response to ocean warming has not been compared to 3-D ocean–ice-sheet coupled models. Here, we assess various melting parameterisations ranging from simple scalings with far-field thermal driving to emulators of box and plume models, using a new coupling framework co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(154 citation statements)
references
References 70 publications
4
132
2
Order By: Relevance
“…However, we have not investigated the impact of uncertainty in the melt rate forcing anomaly added during the extended simulations. Accounting for different ocean temperature projections is likely to add considerable spread to the distribution of future sea level contribution 10.1029/2019GL084941 (Holland et al, 2019), whereas the precise form of the ocean melt parameterization is likely to be less influential (Favier et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have not investigated the impact of uncertainty in the melt rate forcing anomaly added during the extended simulations. Accounting for different ocean temperature projections is likely to add considerable spread to the distribution of future sea level contribution 10.1029/2019GL084941 (Holland et al, 2019), whereas the precise form of the ocean melt parameterization is likely to be less influential (Favier et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The CMIP5 ensemble consists of 50 AOGCMs and Earth system models (ESMs) from 21 modelling groups (Taylor et al, 2012), providing a valuable resource for exploring the projected future evolution of the climate under varying future emission scenarios. Biases in the representation of climatological features in the Southern Ocean have been widely investigated (Bracegirdle et al, 2013;Hosking et al, 2013;Little and Urban, 2016;Meijers et al, 2012;Sallée et al, 2013aSallée et al, , 2013b, and individual model representation of observed climate varies largely across the ensemble (Flato et al, 2013). Comparing the output of AOGCMs against climatological observations provides a means by which we can investigate biases, assess model performance (Gleckler et al, 2008) and identify models that best reproduce observed climate in the Southern Ocean.…”
Section: Cmip5 Subsetmentioning
confidence: 99%
“…The ice-sheet physics is conventional in the sense that it includes well-understood retreat mechanisms such as MISI, but not hydrofracture or cliff collapse (Pollard et al, 2015;Pollard and DeConto, 2016). Some important long-term feedbacks such as solid-Earth 5 rebound and relative-sea-level changes (Gomez et al, 2010;Larour et al, 2019) are omitted, and there is no ice-ocean coupling (e.g., De Rydt and Gudmundsson, 2016;Seroussi et al, 2017;Favier et al, 2019). Thus, the timing and magnitude of simulated ice sheet retreat are imprecise, but we can identify responses that are robust across simulations, and also draw attention to the largest sources of uncertainty.…”
mentioning
confidence: 99%